Induction of shoot buds multiplication of eusideroxylon zwageri tesym. & binned (Borneo ironwood) by using nodal explants - Gibson, Entuni; Rebicca, Edward (by MedCrave Group, 2016)
Eusideroxylon zwageri is a tree of the tropical rainforest which is belongs to a family of Lauraceae. This species is one of the hardest timber species in Southeast Asia and unfortunately endangered in some part of Southeast Asia. The objective of this study was to determine the optimal culture medium for the induction of shoot buds from nodal explants of E. zwageri. Different concentrations and combinations of BAP (1.0, 2.0, 3.0, 4.0, 5.0 and 6.0mg/L) alone or either in combination with NAA (0.5mg/L) or IBA (0.5mg/L) were used in order to induce multiple shoot buds of this species. The nodal explants were collected from the healthy lateral branches of two to three years old of E. zwageri sapling. The finding in this multiple shoot buds study showed that MS medium which have been supplemented with 5.0mg/L of BAP alone or in combination with either 0.5mg/L of NAA or IBA had induced the highest mean number of shoots buds and mean number of leaves respectively. It can be recommended that studies on plantlet regeneration of this species should be conducted and field performance should be carried out on this regenerated species.